Rehearsal development as development of iterative recall processes - Lehmann, Martin (Frontiers in Psychology, 2015)
Although much is known about the critical importance of active verbal rehearsal for successful recall, knowledge about the mechanisms of rehearsal and their respective development in children is very limited. To be able to rehearse several items together, these items have to be available, or, if presented and rehearsed previously, retrieved from memory. Therefore, joint rehearsal of several items may itself be considered recall. Accordingly, by analyzing free recall, one cannot only gain insight into how recall and rehearsal unfold, but also into how principles that govern children’s recall govern children’s rehearsal. Over a period of three and a half years (beginning at grade 3) 54 children were longitudinally assessed seven times on several overt rehearsal free recall trials. A first set of analyses on recall revealed significant age-related increases in the primacy effect and an age-invariant recency effect. In the middle portion of the list, wave-shaped recall characteristics emerged and increased with age, indicating grouping of the list into subsequences. In a second set of analyses, overt rehearsal behavior was decomposed into distinct rehearsal sets. Analyses of these sets revealed that the distribution of rehearsals within each set resembled the serial position curves with one- or two-item primacy and recency effects and wave-shaped rehearsal patterns in between. In addition, rehearsal behavior throughout the list was characterized by a decreasing tendency to begin rehearsal sets with the first list item. This result parallels the phenomenon of beginning recall with the first item on short lists and with the last item on longer lists.